IMPACT OF COVID 19 ON MENTAL HEALTH OF CHILDREN - Mrs. S. Shabna ,; Dr. P. Christuraj, (IJRDO - Journal of Social Science and Humanities Research, 2021)
The coronavirus disease 2019 (COVID-19) outbreak was first reported in Wuhan, China, and was later reported to have spread throughout the world to create a global pandemic. Several countries declared this pandemic as a national emergency, forcing millions of people to go into lockdown. This unexpected imposed social isolation has caused enormous disruption of daily routines for the global community, especially children. Among the measures intended to reduce the spread of the virus, most schools closed, cancelled classes, and moved it to home-based or online learning to encourage and adhere to social distancing guidelines. Education and learnings of 67.6% of students are impacted globally due to coronavirus in 143 countries. The transition away from physical classes has significantly disrupted the lives of students and their families, posing a potential risk to the mental well-being of children. An abrupt change in the learning environment and limited social interactions and activities posed an unusual situation for children's developing brains. It is essential and obligatory for the scientific community and healthcare workers to assess and analyze the psychological impact caused by the coronavirus pandemic on children and adolescents, as several mental health disorders begin during childhood. Countries across the globe, including the United States, are in the dilemma of determining appropriate strategies for children to minimize the psychological impact of coronavirus. The design of this review is to investigate and identify the risk factors to mental health and propose possible solutions to avoid the detrimental consequence of this crisis on the psychology of our future adult generations.